(a+b+c)^3-a^3-b^3-c^3
Answers
Answered by
0
hey here is ur answer
=(a+b+c)^3-a^3-b^3-c^3
=(a+b+c)^3 -(a+b+c)^3
=>0
mark it as a brainliest Tarun
=(a+b+c)^3-a^3-b^3-c^3
=(a+b+c)^3 -(a+b+c)^3
=>0
mark it as a brainliest Tarun
tarunpreetkaur9:
Its wrong Sanjanaojha
Answered by
1
Answer:
Step-by-step explanation:
Consider:
(a+b+c)3 - a3-b3-c3 = [(a+b)+c]3 – a3-b3-c3
(a+b)3+c3+3c(a+b)(a+b+c)-a3-b3-c3
A3+b3+3ab(a+b)+c3+3c(a+b)(a+b+c)-a3-b3-c3
A3+b3+c3+3ab(a+b)+3c(a+b)(a+b+c)-a3-b3-c3
3ab(a+b)+3c(a+b)(a+b+c) 3(a+b)[ab+c(a+b+c)]
3(a+b)[ab+ac+bc+c2] 3(a+b)[a(b+c)+c(b+c)]
3(a+b)(b+c)(c+a)
Similar questions